Avaliação da atividade antioxidante do extrato de erva-cidreira-de-arbusto (Lippia alba (Mill) NE Brown) em embutido cozido a base de carne ovina de descarte - Oliveira, Cristiane Ayala de (2011)
The present paper has the goal evaluate the use of the disposal sheep meat in fitted meat and evaluate its lipid stability through the using of lemon balm bush extract (Lippia alba (Mill) NE Brown). In a first moment was accomplished a characterization of the lemon balm bush extract with the concentrations of 70%, 80% and 90% of ethanol, of their Phenol compositions and total Flavonoid. The extract were also characterized how about their antioxidant activity through the kidnap technique of free radical DPPH .After the extracts being compared the one that got a better result was used in concentrations 0,25%, 0,5% e 0,75% in the manufactured of fitted meat with disposal ovine meat than analyzed on refrigerated stored. The chemistry psycho analyses of the fitted meat were composed by humidity, protein, ash, fattening, pH, and water activity (Aw) TBARS, color and objective texture. The acceptable products tests were determined through the sensorial analysis by the multiple comparison test and acceptable index. The analysis were accomplished in the 1º, 10º, 20º and 30º days of store with the microbiology analysis The results gotten in the centesimal composition of products are according with the demand from the Brazilian Legislation related to the color of the product this presents a coloration with a reddish tonality that is darker and a ruddy with more predomination of red tonality (a*). The values gotten of pH (6,53±0,07) and Aw (0,93±0,004) are according with the expected to the production of fitted meat. The values gotten with Staphylococcus coagulase positive; Salmonella; Total Coliforms and fecal coliforms are founded in a low value to the established limits by the legislation. The acceptable index (IA%) to the attributes of color , flavor and texture were higher to 70%, however the aroma of the product to all the treatments presented the unsatisfied values what it could be more improved. Concluded that is possible elaborated a fitted meat based on ovine meat with the using of 60% of the hock meat and 40% of ovine pallet.